Children's Parasocial Breakups With Media Characters From the Perspective of the Parent. (March 2019) - Aguiar, Naomi R.; Richards, Melissa N.; Bond, Bradley J.; Putnam, Marisa M.; Calvert, Sandra L.
Children's parasocial relationships (PSRs) with media characters end through a process called PSR breakups. An online parent report measure was used to describe preschool and school-aged children's breakups with media characters, as well as the attributes of past and current favorite characters. According to parents ( N = 138), 51% of children experienced PSR breakups. PSRs lasted about two years before a breakup occurred. Past and current favorite characters were animated, human-like, and embedded in fantastical content. Current favorite characters taught fewer academic lessons than past favorite characters. Both boys and girls had current favorite characters that were more gendered in their physical appearance than past favorite characters. However, girls' current favorite characters had more masculine traits than past favorite characters. Our findings suggest possible avenues for the design of future media characters that can teach as they entertain.